The Application of a Problem-Based Learning Model to Enhance Student Engagement in Pancasila and Civic Education Classes - Nurhidayah, Nurhidayah; Murdiono, Mukhamad (International Journal of Social Service and Research, 2026)
The purpose of this study is to analyze and describe the implementation of problem-based learning (PBL) in increasing student learning participation in Pancasila and Citizenship Education subjects. The research employed a mixed-methods approach, combining qualitative and quantitative methods. The study was conducted in class VIII C of SMP Negeri 1 Mlati, Sleman, Yogyakarta. Data were collected through observation, documentation, and questionnaires. The results show that the problem-based learning model is able to increase student learning participation, with the highest score reaching 76.7%. This result meets the criteria for the "high" category in student participation achievement. Problem-based learning encourages students to discuss, collaborate, ask questions, express opinions, provide input, make presentations, and become more active and creative. The implication of this study is that PBL can be effectively implemented as a student-centered learning strategy to address low participation in civic education, particularly in classroom settings where passive learning has been prevalent. After implementing problem-based learning, students experienced many positive changes in their learning behavior and engagement